O2‐sensitive MRI distinguishes brain tumor versus radiation necrosis in murine models. Issue 6 (12th May 2016) - Beeman, Scott C.; Shui, Ying‐Bo; Perez‐Torres, Carlos J.; Engelbach, John A.; Ackerman, Joseph J. H.; Garbow, Joel R.
Abstract : Purpose: The goal of this study was to quantify the relationship between the 1 H longitudinal relaxation rate constant, R1, and oxygen (O2 ) concentration (relaxivity, r1 ) in tissue and to quantify O2 ‐driven changes in R1 (ΔR1 ) during a breathing gas challenge in normal brain, radiation‐induced lesions, and tumor lesions. Methods: R1 data were collected in control‐state mice (n = 4) during three different breathing gas (and thus tissue O2 ) conditions. In parallel experiments, pO2 was measured in the thalamus of control‐state mice (n = 4) under the same breathing gas conditions using an O2 ‐sensitive microprobe. The relaxivity of tissue O2 was calculated using the R1 and pO2 data. R1 data were collected in control‐state (n = 4) mice, a glioma model (n = 7), and a radiation necrosis model (n = 6) during two breathing gas (thus tissue O2 ) conditions. R1 and ΔR1 were calculated for each cohort. Results: O2 r1 in the brain was 9 × 10 −4  ± 3 × 10 −4 mm Hg −1 · s −1 at 4.7T. R1 and ΔR1 measurements distinguished radiation necrosis from tumor (P< 0.03 and P< 0.01, respectively). Conclusion: The relaxivity of O2 in the brain is determined. R1 and ΔR1 measurements differentiate tumor lesions from radiation necrosis lesions in the mouse models. These pathologies are difficult to distinguish by traditional imaging techniques; O2 ‐driven changes in R1 holds promise in this regard. Magn Reson Med 75:1–2, 2016. © 2015 Wiley Periodicals, Inc.